Analisis Efektivitas Biaya Haloperidol-Chlorpromazine dengan Haloperidol-Risperidone pada Pasien Skizofrenia di Rumah Sakit dr. H. Marzoeki Mahdi Bogor - Fitriani Putri; Delina Hasan; Ahmad Fuad Afdhal; Lahargo Kembaren (Fakultas Farmasi Universitas Pancasila, 2020)
Schizophrenia is a disease that requires a long treatment time, this will have an impact on drug use and costs in the long term. Therefore it is necessary to find an alternative drug that is eff ective and effi cient by using pharmacoeconomics methods, that is cost-eff ectiveness analysis. The purpose of this study was to determine which of the two combination drugs was eff ective and effi cient for the treatment of schizophrenic patients in hospital Marzoeki Mahdi Bogor. This research method used cross sectional design, the sample size in this study was 90 schizophrenic patients obtained from patient medical records and data collected prospectively from dr. H. Marzoeki Mahdi in 2019. Samples were divided equally into two groups, one group received haloperidol - chlorpromazine and the second group received haloperidol - risperidone. The eff ectiveness parameter used in this study is the GAF (Global Assessment of Functioning) value. The results showed that the combination of haloperidol - risperidone was more eff ective than the combination of haloperidol - risperidone, this was evidenced by an increase in the patients GAF value by 95.5% (43 patients) with an average diff erence between the initial and fi nal GAF values of 6.89, while the combination of haloperidol - chlorpromazine amounted to 93.3% (42 patients) with an average diff erence between the initial and fi nal GAF values of 5.84. The ACER value of haloperidol - chlorpromazine is Rp. 6,587,753 and the ACER value for the haloperidol – risperidone combination is Rp. 6,148,897. In conclusion, the haloperidol - risperidone combination is more cost eff ective (p < 0.05) than the haloperidol - chlorpromazine combination.